Host Factors of Favorable Intestinal Microbial Colonization - Pirr, Sabine; Viemann, Dorothee (Frontiers in Immunology, 2020)
Gut microbial colonization starts with birth and initiates a complex process between the host and the microbiota. Successful co-development of both establishes a symbiotic mutual relationship and functional homeostasis, while alterations thereof predispose the individual life-long to inflammatory and metabolic diseases. Multiple data have been provided how colonizing microbes induce a reprogramming and maturation of immunity by providing crucial instructing information to the newborn immune system. Less is known about what host factors have influence on the interplay between intestinal immunity and the composition of the gut microbial ecology. Here we review existing evidence regarding host factors that contribute to a favorable development of the gut microbiome and thereby successful maturation of gut mucosal immunity.